ANALISIS PENGALAMAN PETANI ORGANIK: EKSPLORASI PENGALAMAN PETANI ORGANIK DENGAN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS - Rais, Muhammad Rifai; Darwanto, Darwanto (Universitas Dian Nuswantoro Semarang, 2016)
The organic farming system is an agricultural system that keeps the environment-friendly. The organic farming system is expected to be a solution for building agriculture and improving the welfare of farmers. This study aims to explore and understand the experience gained by individuals in living organic farming systems. The study used the Interpretative Phenomenological Analysis (IPA) approach that aims thedepth of meaning against various backgrounds, experiences, unique events, and subject thinking through in- depth interviews. The results found that the organic farming systemapplicationled to a variety of the organic farming system experience.Organic farming systems that have been implemented at the moment are still constrained so that social capital in the form of values, norms, trusts and social networks play a role in overcoming these obstacles. Development of organic agriculture is expected to encourage economic aspects, health aspects, and ecological aspects.Keywords: Organic Farming; Experience; Social Capital; Phenomenological